Patient-Reported Outcomes and Satisfaction after Cervical Epidural Steroid Injection for Cervical Radiculopathy: - Hosseinpoor, Ali; Hashemi, Masoud; Dadkhah, Payman; Taheri, Mehrdad; Ghasemi, Mahshid; Farjam, Mojtaba (Galen Medical Journal, 2019)
Background: Cervical radiculopathy caused by disc herniation is a frequent public health issue with economical and socio-professional impacts. The objective of the present study is to evaluate the patient-reported outcomes and satisfaction from cervical epidural steroid injection during a 2-year follow-up. Materials and Methods: Results based on patientsâ€™ reports from a previously performed intervention of cervical epidural steroid injection on patients with cervical radiculopathy due to cervical disc herniation are prospectively collected. Outcome measures are Neck Disability Index (NDI), numerical rating scale (NRS) for pain assessment, and 5-scale patient satisfaction questionnaire (PSQ) plus opioid medication for pain relief, additional injections, and progression to surgery. Results: Of total 37 cases, 34 were available for follow-up after 2-year postoperatively. The mean preoperative NDI was 21.17 and improved to 17.38, and the mean NRS was 7.7 and improved to 5.00; both were statistically significant. Mean patient satisfaction after 2 years was 3.17 out of 5. 11 cases needed additional injections, and 4 of patients proceeded to surgery. Conclusion: We showed that transforaminal cervical epidural steroid injection for cervical radiculopathy is an effective non-surgical treatment option, providing significant pain relief and functional improvement during 2-years follow-up along with higher-than-average patient satisfaction in most of our patients. [GMJ.2019;8:e1478]Â 